Students managing work and study role boundaries: a person-centred approach - Creed, Peter A.; Hood, Michelle; Bialocerkowski, Andrea; Machin, M. Anthony; Brough, Paula; Kim, Sujin; Winterbotham, Sonya; Eastgate, Lindsay (Frontiers in Psychology, 2023)
To cope with the demands of both study and part-time work, students need to structure their role boundaries (e.g., integrate vs. segment their roles) to meet their needs. As students differ on how well they manage this, we examined whether there were different clusters of students based on role boundary characteristics. We assessed a large sample of working students (N = 808; 76% female; MAge 19.6 years) on measures of work and study boundary congruence and flexibility. Four distinct groups emerged: (a) “balanced” (65.4%) with moderate levels of congruence and flexibility; (b) “high work congruence and flexibility” (17.5%) with supportive working arrangements; (c) “low work congruence and flexibility” (9.7%) with low levels of workplace support; and (d) “low study congruence” (7.3%) with low levels of study support. These four groups differed on five outcome variables (work/study demands, role conflict, study burnout, and perceived future employability), with the “balanced” and “high work congruence and flexibility” groups generally scoring more positively, and the “low work congruence and flexibility” and the “low study congruence” groups reporting more negative outcomes. Our results suggest that different groups of students need different types of support to help them effectively cope with their multiple role responsibilities.